2007
DOI: 10.1111/j.1601-183x.2007.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of neuronal and peripheral serotonin synthesis in Drosophila melanogaster

Abstract: In Drosophila, one enzyme (Drosophila tryptophan-phenylalanine hydroxylase, DTPHu) hydroxylates both tryptophan to yield 5-hydroxytryptophan, the first step in serotonin synthesis, and phenylalanine, to generate tyrosine. Analysis of the sequenced Drosophila genome identified an additional enzyme with extensive homology to mammalian tryptophan hydroxylase (TPH), which we have termed DTRHn. We have shown that DTRHn can hydroxylate tryptophan in vitro but displays differential activity relative to DTPHu when usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
109
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(122 citation statements)
references
References 74 publications
(91 reference statements)
8
109
0
Order By: Relevance
“…he phenylalanine-hydroxylating system catalyzes the irreversible hydroxylation of phenylalanine to tyrosine, which is the rate-limiting step in animal phenylalanine catabolism and protein and neurotransmitter biosynthesis and results in the formation of one molecule of fumarate and one of acetylcoenzyme A (CoA) from each molecule of phenylalanine (1,2). The animal phenylalanine-hydroxylating system consists of several essential components: phenylalanine hydroxylase (PAH) (EC 1.14.16.1), pterin-4␣-carbinolamine dehydratase (PCD) (EC 4.2.1.96), dihydropteridine reductase (DHPR) (EC 1.5.1.34), and the obligatory cofactors tetrahydrobiopterin (BH 4 ) and molecular oxygen (3,4) (Fig.…”
mentioning
confidence: 99%
“…he phenylalanine-hydroxylating system catalyzes the irreversible hydroxylation of phenylalanine to tyrosine, which is the rate-limiting step in animal phenylalanine catabolism and protein and neurotransmitter biosynthesis and results in the formation of one molecule of fumarate and one of acetylcoenzyme A (CoA) from each molecule of phenylalanine (1,2). The animal phenylalanine-hydroxylating system consists of several essential components: phenylalanine hydroxylase (PAH) (EC 1.14.16.1), pterin-4␣-carbinolamine dehydratase (PCD) (EC 4.2.1.96), dihydropteridine reductase (DHPR) (EC 1.5.1.34), and the obligatory cofactors tetrahydrobiopterin (BH 4 ) and molecular oxygen (3,4) (Fig.…”
mentioning
confidence: 99%
“…As in other species, serotonergic neurons in the fly nervous system display arbors of processes that ramify widely in multiple neuropil areas. Earlier studies from several laboratories, including ours, showed that manipulating total populations of 5HT neurons in Drosophila influence a wide variety of different behaviors [7][8][9][10][11][12] . How do serotonergic neurons function to exert such a wide spectrum of behavioral actions?…”
mentioning
confidence: 76%
“…Interestingly TPH is required for early development, implying that both serotonin and dopamine are required in non-neuronal cells during development itself [23,104,105]. TRH-null flies are viable and fertile with diminished locomotion and feeding behavior [105]. Overexpression of TRH in serotonergic neurons results in increased cytoplasmic serotonin levels, leading to spheroid formation, i.e.…”
Section: The Serotonergic Systemmentioning
confidence: 99%
“…anxiety-like behavior [109]. This may appear counterintuitive, because reduction in neuronal serotonin is associated with decreased locomotion [105], but it highlights the doubled-edged nature of transporter deficiency/inhibition: the plasmalemmal monoamine transporters are required for both, termination of synaptic signaling by removing the neurotransmitter and for replenishing the vesicular pool by operating in relay with VMAT. The symptoms of Parkinsonism, which are seen in the human dopamine transporter deficiency syndrome (see above), highlight the importance of the dopamine transporter in maintaining the vesicular dopamine pool.…”
Section: The Serotonergic Systemmentioning
confidence: 99%